2021
DOI: 10.1111/gbi.12478
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting nutrient availability between marine and brackish waters in the late Mesoproterozoic: Evidence from the Paranoá Group, Brazil

Abstract: Understanding the delayed rise of eukaryotic life on Earth is one of the most fundamental questions about biological evolution. Numerous studies have presented evidence for oxygen and nutrient limitations in seawater during the Mesoproterozoic era, indicating that open marine settings may not have been able to sustain a eukaryotic biosphere with complex, multicellular organisms. However, many of these data sets represent restricted marine basins, which may bias our view of habitability. Furthermore, it remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 94 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…For example, sulfate concentrations in the Archean ocean may have been over 3 orders of magnitude lower than today, and nitrate was probably limited to rare oxygen oases in surface waters. , At that time, sulfate and nitrate would likely have acted as nonconservative species in seawater with markedly shorter residence times and response times to nonmarine conditions. Both nitrate and sulfate concentrations increased in seawater around the time of the Paleoproterozoic Great Oxidation Event , and probably reached modern levels in the Neoproterozoic or Phanerozoic during the second rise of oxygen. , In a previous study, we showed that late Proterozoic marine sulfate levels (at ∼1.1 Ga) were high enough to leave a significant mark in brackish environments, where trace elements and nitrogen isotopes revealed a nonmarine influence . Hence the modern hierarchy of proxy response time was perhaps established by that point; however, care is nevertheless required in deep-time studies at variable stratigraphic resolution.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…For example, sulfate concentrations in the Archean ocean may have been over 3 orders of magnitude lower than today, and nitrate was probably limited to rare oxygen oases in surface waters. , At that time, sulfate and nitrate would likely have acted as nonconservative species in seawater with markedly shorter residence times and response times to nonmarine conditions. Both nitrate and sulfate concentrations increased in seawater around the time of the Paleoproterozoic Great Oxidation Event , and probably reached modern levels in the Neoproterozoic or Phanerozoic during the second rise of oxygen. , In a previous study, we showed that late Proterozoic marine sulfate levels (at ∼1.1 Ga) were high enough to leave a significant mark in brackish environments, where trace elements and nitrogen isotopes revealed a nonmarine influence . Hence the modern hierarchy of proxy response time was perhaps established by that point; however, care is nevertheless required in deep-time studies at variable stratigraphic resolution.…”
Section: Discussionmentioning
confidence: 66%
“… 54 , 55 In a previous study, we showed that late Proterozoic marine sulfate levels (at ∼1.1 Ga) were high enough to leave a significant mark in brackish environments, where trace elements and nitrogen isotopes revealed a nonmarine influence. 56 Hence the modern hierarchy of proxy response time was perhaps established by that point; however, care is nevertheless required in deep-time studies at variable stratigraphic resolution.…”
Section: Discussionmentioning
confidence: 99%
“…7. Compilation of sedimentary δ 15 N data through the Mesoproterozoic with data from ~1560Ma, ~1460 Ma and ~1380 Ma Yanliao Basin, China(Luo et al, 2015;Wang et al, 2020b;Shi et al, 2021; Zhang et al, 2021 and this study), ~1500Ma Bangemall basin and ~1450 Ma Roper Basin, Australia(Koehler et al, 2017), ~1400 Ma Belt Basin, USA(Stüeken, 2013), ~1200 Ma Vindhyan Basin, India(Gilleaudeau et al, 2020), ~1100 Ma Paranoá Group, Brazil(Stüeken et al, 2021) and~1048 Ma Borden Basin, Canada (Hodgskiss et al, 2020. The orange area represents the typical range of nitrogen fixation.…”
mentioning
confidence: 50%
“…LOWESS analysis of the lowest quartile data revealed a stepwise increase in δ 15 N values around 800 Ma, from less than 2 to ~3‰. The deviation in the 1.1- to 1.2-Ga time bin is probably related to sampling bias: data in this time bin come from only one section that was deposited in a well-oxygenated basin ( 67 ). Because of the scarcity of data in the 800- to 900-Ma time bin, the bootstrapped LOWESS result indicates that the rise in δ 15 N could have started as early as 900 Ma, but a changepoint detection analysis revealed that the most significant change in the mean and variance of the lowest 25% δ 15 N data occurred at ca.…”
Section: Discussionmentioning
confidence: 99%